A STRATEGY FOR UNLOCKING LOGISTICS IN UKRAINE IN THE FACE OF RISKS AND THREATS - PAVLOV, Kostiantyn; TOTSKA, Olesia; BORTNIK, Anton; BURTSEV, Oleksandr; MOROZ, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The current realities of economic functioning, especially under the conditions of a full-scale war in Ukraine and global political and economic instability, impose new demands on the organization of logistics processes. Logistics, as a key element in ensuring the effective operation of enterprises, plays a crucial role in maintaining the continuity of production, supply, and distribution of goods. In light of the destruction of transport and warehouse infrastructure, disruption of traditional delivery routes, and the need to adapt to new risks, logistics management has become a critically important function that requires revising approaches and implementing innovative solutions.The urgency of the research is particularly evident in the context of the need for enterprises to adapt to crisis phenomena, which have both internal and external origins. In this regard, the article is devoted to the issues of strategic directions for the development of logistics in Ukraine under the current conditions of economic activity, characterized by constant risks. The study's relevance and the existence of previously unresolved components of the general problem have determined the purpose of this article: to investigate the adaptation processes of enterprises' logistics strategies under crisis conditions, monitor the current state of logistics services, and outline strategic approaches to improving logistics processes.The study outlines key and problematic issues enterprises face in logistics under current conditions, especially during martial law. It explores the peculiarities of ensuring logistics chains' uninterrupted functioning and ability to withstand crises. The main factors influencing enterprises' formation and implementation of logistics strategies are highlighted. Strategic measures of state regulation and support are proposed, aimed at expanding the adaptive capacity and effectiveness of logistics operations of small and medium-sized enterprises. These directions are based on key aspects such as supply chain optimization and financial and institutional support. Best practices and successful adaptation cases of enterprise logistics strategies to crises, particularly martial law, are recommended.
Keywords: logistics; enterprises; crisis; martial law; adaptation; logistics strategies